Obesogenic Diets Cause Alterations on Proteins and Theirs Post-Translational Modifications in Mouse Brains. (May 2021) - Siino, Valentina; Jensen, Pia; James, Peter; Vasto, Sonya; Amato, Antonella; Mulè, Flavia; Accardi, Giulia; Larsen, Martin Røssel
Obesity constitutes a major global health threat and is associated with a variety of diseases ranging from metabolic and cardiovascular disease, cancer to neurodegeneration. The hallmarks of neurodegeneration include oxidative stress, proteasome impairment, mitochondrial dysfunction and accumulation of abnormal protein aggregates as well as metabolic alterations. As an example, in post-mortem brain of patients with Alzheimer's disease (AD), several studies have reported reduction of insulin, insulin-like growth factor 1 and insulin receptor and an increase in tau protein and glycogen-synthase kinase-3β compared to healthy controls suggesting an impairment of metabolism in the AD patient's brain. Given these lines of evidence, in the present study we investigated brains of mice treated with 2 obesogenic diets, high-fat diet (HFD) and high-glycaemic diet (HGD), compared to mice fed with a standard diet (SD) employing a quantitative mass spectrometry-based approach. Moreover, post-translational modified proteins (phosphorylated and N-linked glycosylated) were studied. The aim of the study was to identify proteins present in the brain that are changing their expression based on the diet given to the mice. We believed that some of these changes would highlight pathways and molecular mechanisms that could link obesity to brain impairment. The results showed in this study suggest that, together with cytoskeletal proteins, mitochondria and metabolic proteins are changing their post-translational status in brains of obese mice. Specifically, proteins involved in metabolic pathways and in mitochondrial functions are mainly downregulated in mice fed with obesogenic diets compared to SD. These changes suggest a reduced metabolism and a lower activity of mitochondria in obese mice. Some of these proteins, such as PGM1 and MCT1 have been shown to be involved in brain impairment as well. These results might shed light on the well-studied correlation between obesity and brain damage. The results presented here are in agreement with previous findings and aim to open new perspectives on the connection between diet-induced obesity and brain impairment.